Assessment of indigenous farming practices for foxtail millet (Setaria italica) in North Cotabato, Philippines - JOEFREY F. HABIBUN; MARIA ESTELA B. DETALLA; AGRIPINA A. ARADILLA; MA. STELA M. PAULICAN; JUDITH D. INTONG (Asian Journal of Agriculture, 2026)
Abstract. Habibun JF, Detalla MEB, Aradilla AA, Paulican MSM, Intong JD. 2026. Assessment of indigenous farming practices for foxtail millet (Setaria italica) in North Cotabato, Philippines. Asian J Agric 10 (1): g100162. https://doi.org/10.13057/asianjagric/g100162. This study assessed and verified indigenous farming practices of Manobo farmers for foxtail millet (Setaria italica) production in President Roxas, North Cotabato, Philippines. A participatory on-farm trial was conducted to evaluate performance of farmers' practice (indigenous planting methods) and local millet lines in the on-farm environment. The experiment was laid out in strip plot in Randomized Complete Block Design (RCBD) arrangement with four replications. Three local millet lines (yellow, black and red) were tested in three planting methods; broadcast, hill and drill planting methods. Results showed no significant differences among millet lines and planting methods in terms of emergence (5.92-6.00 Days to emergence (DAS)), panicle emergence (81-82 DAS), maturity (103-104 DAS), plant height, and tillers number. However, planting method has a significant effect on yield and economic return of foxtail millet. The highest yield of 2,319.50 kg ha-1 and ROI of 124.15% was obtained from drill planting, followed by broadcast planting (2,189.08 kg ha-1) but with significantly low yield from hill planting (1,667.25 kg ha-1). Farmer feedback further confirmed that drill planting improved plant spacing, enhanced weed control, and promoted better soil moisture utilization under field conditions but more labor is required for planting. These findings support integrating validated indigenous practices into extension programs for sustainable agriculture.